Edukasi Pencegahan Kekerasan Seksual Sejak Dini pada Anak dengan Metode Story Telling - Devita, Yeni; Puswati, Desti; Nita, Yureya; Alfianur, Alfianur (ADMA : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2023)
Child sexual abuse has repercussions both psychologically and physically. Child sexual abuse should be prevented early. One of the prevention efforts is to provide education using the story telling method. The purpose of this community service activity is to provide information to children so that they can avoid sexual violence behavior. The method of implementing this activity is carried out in 3 stages including the preparation, implementation, and evaluation stages. The implementation of storytelling is carried out by the video method. In this video, it is told how a child can become a victim of sexual violence. In this video, we also teach how children prevent sexual violence behavior. This story telling is given for 90 minutes. The results of the activity showed an increase in children's knowledge about sexual violence and its prevention. It is hoped that the school can carry out this story telling regularly.